Parkinson's Disease, NOTCH3 Genetic Variants, and White Matter Hyperintensities. Issue 11 (23rd June 2020) - Ramirez, Joel; Dilliott, Allison A.; Binns, Malcolm A.; Breen, David P.; Evans, Emily C.; Beaton, Derek; McLaughlin, Paula M.; Kwan, Donna; Holmes, Melissa F.; Ozzoude, Miracle; Scott, Christopher J.M.; Strother, Stephen C.; et al.
Abstract: Background: White matter hyperintensities (WMH) on magnetic resonance imaging may influence clinical presentation in patients with Parkinson's disease (PD), although their significance and pathophysiological origins remain unresolved. Studies examining WMH have identified pathogenic variants in NOTCH3 as an underlying cause of inherited forms of cerebral small vessel disease. Methods: We examined NOTCH3 variants, WMH volumes, and clinical correlates in 139 PD patients in the Ontario Neurodegenerative Disease Research Initiative cohort. Results: We identified 13 PD patients (~9%) with rare (<1% of general population), nonsynonymous NOTCH3 variants. Bayesian linear modeling demonstrated a doubling of WMH between variant negative and positive patients (3.1 vs. 6.9 mL), with large effect sizes for periventricular WMH ( d = 0.8) and lacunes ( d = 1.2). Negative correlations were observed between WMH and global cognition ( r = −0.2). Conclusion: The NOTCH3 rare variants in PD may significantly contribute to increased WMH burden, which in turn may negatively influence cognition. © 2020 International Parkinson and Movement Disorder Society